2019
DOI: 10.1080/03019233.2019.1604614
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of centre segregation in continuous casting bloom and the resulting carbide homogeneity in bearing steel GCr15

Abstract: In the present work, solidification structure and centre segregation in continuously cast bearing steel GCr15 blooms with 220mm×260 mm were obtained by different casting conditions (M-EMS, M + F-EMS, M + F-EMS + MSR), which were systematically optimized by numerical simulation and experiments. The relationship between centre segregation in continuously cast GCr15 bloom, heredity in hot-rolled steel and carbide inhomogeneity of hot-rolled steel with was investigated comprehensively. Results showed that compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The central region of a bloom will generally contain a high number of centerline voids and a high degree of segregation, [33][34][35] as shown in Figure 2a, the round bloom produced for this study featured both centerline voids and segregation. Many of the solidification phenomena, structural features, and macrosegregation patterns found in continuously cast round blooms were found in cast ingots, although to a less pronounced, degree, and segregation could be found in the longitudinal sections of continuously cast steel.…”
Section: Methodsmentioning
confidence: 81%
“…The central region of a bloom will generally contain a high number of centerline voids and a high degree of segregation, [33][34][35] as shown in Figure 2a, the round bloom produced for this study featured both centerline voids and segregation. Many of the solidification phenomena, structural features, and macrosegregation patterns found in continuously cast round blooms were found in cast ingots, although to a less pronounced, degree, and segregation could be found in the longitudinal sections of continuously cast steel.…”
Section: Methodsmentioning
confidence: 81%
“…Based on the above analysis, the hereditary equations for the longitudinal fluctuation of carbon in the columnar crystal zone, equiaxed crystal zone, and the centerline of the billet during the rolling process can be summarized, proposing a general equation. Equation (11) shows the obtained hereditary equations of the longitudinal carbon fluctuation in the columnar and equiaxed crystal zones, and the hereditary equation in the centerline is shown in Equation (12).…”
Section: Hereditary Equation Of Longitudinal Carbon Fluctuationmentioning
confidence: 99%
“…In previous studies, the hereditary behavior of carbon segregation was qualitatively investigated by the microstructural evolution of billets and rolled products [7][8][9][10] and the carbon correspondence between the segregation point of the billets and the segregation band of the rolled products. [11][12][13] For instance, Ji [14] measured the carbon element content on the cross-section of the continuous casting billet by drilling sampling chemical analysis method and analyzed the carbon distribution on the cross-section of the corresponding wire rod by electron probe. The carbon correspondence between the billet and the wire rod qualitatively reflects the hereditary of carbon segregation to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…For GCr15 steel, due to high carbon content, wide mushy zone, and long solidification time, carbon segregation usually occurs during the phase change in continuous casting, resulting in an inhomogeneous distribution of carbon content, where central segregation is the fundamental cause of carbide formation. [8][9][10] Carbide could destroy the continuity of metal, cause stress concentrations, and reduce machinability. Many studies have shown that a rods' internal elements and microstructure homogeneity could be adjusted by controlling the heating and hot-rolling parameters.…”
Section: Introductionmentioning
confidence: 99%